Hunger and war : food provisioning in the Soviet Union during World War II - Goldman, Wendy Z.; Filtzer, Donald A. (Indiana University Press, 2015)
"Making use of recently released Soviet archival materials, Hunger and War investigates state food supply policy and its impact on Soviet society during World War II. It explores the role of the state in provisioning the urban population, particularly workers, with food, and in feeding the Red army; the medicalization of hunger; hunger in blockaded Leningrad; and civilian mortality from hunger and malnutrition in other home front industrial regions. New research reported here challenges and complicates many of the narratives and counter-narratives about the war. The authors engage such difficult subjects as starvation mortality, bitterness over privation and inequalities in provisioning, and conflicts among state organizations. At the same time, they recognize the considerable role played by the Soviet state in organizing supplies of food to adequately support the military effort and defense production, and in developing policies that promoted social stability amid upheaval. The book makes a significant contribution to scholarship on the Soviet population's experience of World War II as well as to studies of war and famine"--Provided by publisher
Keywords: Food supply -- Soviet Union -- History.; World War, 1939-1945 -- Food supply -- Soviet Union.; Rationing -- Soviet Union -- History.; Hunger -- Soviet Union -- History.; Starvation -- History.; Nutrition policy -- Soviet Union -- History.; Food supply -- Political aspects -- Soviet Union -- History.; World War, 1939-1945 -- Social aspects -- Soviet Union.; War and society -- Soviet Union -- History.; Soviet Union -- Social conditions -- 1917-1945.; Guerre mondiale, 1939-1945 -- Alimentation -- URSS.; Rationnement -- URSS -- Histoire.; Faim -- URSS -- Histoire.; Inanition -- Histoire.; Politique alimentaire -- URSS -- Histoire.; Guerre mondiale, 1939-1945 -- Aspect social -- URSS.; Guerre et société -- URSS -- Histoire.; URSS -- Conditions sociales -- 1917-1945.; Aliments -- Approvisionnement -- URSS -- Histoire.; Aliments -- Approvisionnement -- Aspect politique -- URSS -- Histoire.; BUSINESS & ECONOMICS -- Infrastructure.; SOCIAL SCIENCE -- General.; SOCIAL SCIENCE -- Disasters & Disaster Relief.; Food supply; Food supply -- Political aspects; Hunger; Nutrition policy; Rationing; Social aspects; Social conditions; Starvation; War and society; Soviet Union; 1917-1945; History